CRIMINAL LAW POLICY REGARDING THE AUTHORITY OF THE CORRUPTION ERADICATION COMMISSION IN INVESTIGATIONS OF OFFENDERSTHE CRIME OF CORRUPTION IN PROCUREMENT OF MAIN EQUIPMENTBY PERSONNEL OF THE INDONESIAN NATIONAL ARMY - Ilmuwani Lubis; Yasmirah Mandasari Saragih; Karolus Agung Dery Rianto; Irfan Rizky Pradya; Willy Novan Prakoso (RADJA PUBLIKA, 2023)
The Corruption Eradication Commission is an independent institution formed specifically to handle corruption cases which is equipped with a set of authorities in carrying out the duties of investigation, investigation and prosecution. In carrying out the duties and authority of the Corruption Eradication Commission in conducting investigations. perpetrators of corruption, procurement of key TNI equipment and the Military Justice Law, giving rise to pros and cons in various circles. The purpose of writing this thesis is; first, to find out the authority of the Corruption Eradication Commission in investigating perpetrators of corruption in the procurement of defense equipment, especially that carried out by the TNI. Second, to find out the criminal law policy regarding this authority. The Corruption Eradication Commission in investigating perpetrators of corruption in the procurement of TNI defense equipment. In writing this thesis the author used normative juridical research methods which emphasize legal principles, namely the principle of legality. Then it is analyzed qualitatively and conclusions are drawn using a deductive method. The results of the author's research are; First, the investigation carried out by the Corruption Eradication Commission has a legal basis under Article 42 of Law Number 30 of 2002 concerning the Corruption Eradication Commission. All authorities relating to investigations, investigations and prosecutions as regulated in Law Number 8 of 1981 concerning Criminal Procedure Law. also applies to investigators, investigators and public prosecutors within the Corruption Eradication Commission. The criminal law policy regarding the handling carried out by the Corruption Eradication Commission and the TNI regarding corruption cases committed by TNI personnel is a separate treatment. Finally, the author submits a suggestion that the President together with the House of Representatives (DPR) need to establish regulations regarding procedures and procedures for investigations or that existing laws and regulations must be changed so that there are no errors in the authority of investigations by any institution, including the Corruption Eradication Committee, and so that implementation or execution The investigation has a clear legal umbrella and has legal jurisdiction.